Habitat structure and landscape context influence vocalising vertebrates in oil palm plantations - Erin K. Wills; Caitlin S. Willis; Reza Azmi; Dominique A. Potvin; Baizul Hafsyam Badli-Sham; John Howes; Catherine M. Yule; Ben L. Gilby (Biodiversity and Conservation, 2026)
As global food demand rises with population growth, much of the expected land conversion to agriculture is projected to occur in tropical biodiversity hotspots. Balancing food production and biodiversity conservation requires managing agricultural landscapes to serve both goals. To support this, we examined how animal distribution in an oil palm plantation is influenced by landscape context and habitat structure. The study was conducted in Johor, Malaysia, a region dominated by oil palm agriculture. Passive acoustic recorders were deployed across 35 sites within a 1160-hectare oil palm plantation, encompassing a range of yield levels, and distances to natural features. Recordings were collected periodically during the inter-monsoonal period, April-May 2025, targeting peak seasonal and circadian vocal activity of birds and anurans, and analysed using BirdNET and manual spectrogram inspection to identify birds, anurans, and mammals. A total of 89 vertebrate species (75 birds, 12 anurans, 2 mammals) were detected, including several threatened species. Species richness was greatest at sites with taller canopies, lower frond cover, and closer proximity to water and forests, highlighting the importance of maintaining structural complexity and connectivity to maximise biodiversity within plantations. Exploratory analysis found no significant relationship between bird richness, including frugivores, and palm oil yield, thereby suggesting limited short-term effects, though extended studies are required to evaluate longer-term biodiversity influences on production. To enhance biodiversity, we recommend replanting native trees on low-yield blocks, enhancing vertical structure with tree islands, and maintaining clean waterways, while keeping frond stacking to